Language differences, output-orientation, popular TV series, direct school-democracy and research investment in Social Studies – Introduction to an open topics issue - Hedtke, Reinhold; Löfström, Jan; Szukala, Andrea (JSSE - Journal of Social Science Education, 2022)
not necessary